2017
DOI: 10.1007/s00436-017-5376-3
|View full text |Cite
|
Sign up to set email alerts
|

Human cryptosporidiosis in Iran: a systematic review and meta-analysis

Abstract: Cryptosporidiosis caused by Cryptosporidium spp. is an important parasitic disease that can be life-threatening for children and immunocompromised patients. This systematic review and meta-analysis was designed to determine the prevalence rate of Cryptosporidium infection and related risk factors among the Iranian general population. We searched electronic databases including Google Scholar, PubMed, Science Direct, Scopus and Proquest for articles in English and SID, Magiran, IranMedex, and IranDoc for article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 72 publications
0
5
1
2
Order By: Relevance
“…In this sense, research carried out for the refinement of techniques applied to the epidemiological survey to parasitic diseases, such as the strongyloidiasis, is necessary. It should be noted that infection by this parasite is becoming increasingly severe in vulnerable groups, such as immunosuppressed patients, children, and the elderly [5][6][7]. The major concern in these vulnerable groups is the low immune capacity to respond effectively to infectious processes.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, research carried out for the refinement of techniques applied to the epidemiological survey to parasitic diseases, such as the strongyloidiasis, is necessary. It should be noted that infection by this parasite is becoming increasingly severe in vulnerable groups, such as immunosuppressed patients, children, and the elderly [5][6][7]. The major concern in these vulnerable groups is the low immune capacity to respond effectively to infectious processes.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In studies over several years on human specimens from different individuals in terms of contamination with different species of Cryptosporidium in Iran, the prevalence in children, normal people and immunocompromised individuals was 3.65%, 2.94% and 4.54%. 13 A survey on surface water samples in Iran showed that 24 samples (48.98%) of 49 samples were positive for Cryptosporidium spp. 14 Regarding Cryptosporidium, the comparison of the results of the present study with those of other studies on different types of human and water samples in Iran showed that the rate of water contamination was much higher than that of soil contamination and soil contamination than human infection.…”
Section: Discussionmentioning
confidence: 99%
“…Bölgesel ısı ve yağış dağılım değişikliklerinin yıllar içerisinde özellikle su kaynaklı bulaşan Cryptosporidium türleri ile olan enfeksiyonların sıklığı üzerinde etkili olduğu bilinmektedir (12). Bu etkenlerden özellikle Cryptosporidium türleri sağlıklı kişlerde kendi kendini sınırlayan bir ishale sebep olurken iki yaş altı çocuklarda, yaşlılarda ve özellikle bağışıklık sistemi baskılanmış hastalarda hayatı tehdit eden kolera benzeri bir ishal tablosu görülebilmektedir (13). Cryptosporidium sıklığının HIV pozitif bireylerde araştırıldığı çeşitli çalışmalarda oranlar, Malezya'da %3, Endonezya'da %11,9 ve Batı Kamerun'da %2,5 bulunmuştur (14,15,16).…”
Section: Discussionunclassified